Perancangan Sistem Reservasi Tiket pada PT Golden Eagle Indonesia - Sanjaya, Lius Steven; Surja, Stephanie (ComTech: Computer, Mathematics and Engineering Applications, 2013)
This study aims to identify the organization needs of PT Golden Eagle Indonesia to control and manage the data and information of operational transaction. The result of analysis is used as a base for developing a new integrated system that can be the solution for company needs and to face the competition. The activity inanalysis and design is focused in ticket reservation activities, as the main business of the company. These needs will be documented using unified modeling language. There is an expectation that this system will ease the company in doing their activity in ticket reservation. This system will also minimize the data lost and human error usually caused by manual process of transactional data storage.